OPTIMALISASI KEGIATAN PENYELIDIKAN UNIT 3 SUBDIT II GUNA MENINGKATKAN PENGUNGKAPAN PERKARA TINDAK PIDANA NARKOTIKA DI DIREKTORAT RESERSE NARKOBA POLISI DAERAH RIAU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Law of the Republic of Indonesia Number 2 of 2002 concerning the Police which regulates a law enforcement officer has the duty to maintain security and order, enforce the law, provide protection and public services. But the fact is, the professionalism of a law enforcement apparatus such as Investigator unit 3 subdit II, which is still lacking in operational capability of a law enforcement process that does not meet professional standards that can affect the ability to investigate narcotics crime. The purpose of this thesis, namely: First, to what extent is the ability of the investigation activities of unit 3 subdit II in revealing narcotics criminal cases in the Riau Police Directorate of Drug Investigation, Second, What are the factors that hinder the investigation of Narcotics Investigation in order to emphasize drug trafficking, Third, How efforts to optimize the investigation activities of unit 3 subdit II in improving the narcotics crime case handling at the Riau Regional Police Drug Investigation Directorate.This type of research can be classified in the type of sociological juridical research, because in this study the author directly conducts research at a location or a careful place in order to provide a complete and clear picture of the problem under study. This research was conducted at the Riau Police Narcotics Investigation Directorate, while the population and sample were all parties related to the problems examined in this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study were observations, interview and literature study.From the results of the research problem there are three main things that can be concluded. First, the current capability of investigating the disclosure of narcotics crime cases is still inadequate. Such as, the method of investigation that has not been implemented, the inadequacy of facilities and infrastructure and the optimal condition of human resources. Second, the inhibiting factor in emphasizing drug trafficking that affects the performance of personnel is caused by several factors namely internal and external factors. Third, the efforts made to optimize the investigation of narcotic criminal disclosure activities, the need for resources to be repaired, facilities and infrastructure to be repaired, and systems and methods that should also be improved. The author's advice, First, to the Head of the Bureau of human resources in filling the amount of human resources must pay attention to the area and geographical location of the region, because the characteristics between the islands and the mainland are different. Second, increasing the budget, facilities and infrastructure of the distribution of drugs can be overcome. Third, the need for supervision of the implementation of drug criminal investigations, because drug crimes are vulnerable to issues that bring down investigators and the ability of drug dealers to conduct bribery.Keywords: Ability - Investigation - Narcotics Crime